e-Health Literacy Scale, Patient Attitudes, Medication Adherence, and Internal Locus of Control - Donrie J. Purcell; Gesulla Cavanaugh; Kamilah B. Thomas-Purcell; Joshua Caballero; Drenna Waldrop; Victoria Ayala; Rosemary Davenport; Raymond L. Ownby (SLACK Incorporated, 2023)
Background: Health literacy is related to a variety of health outcomes, including disease control, health-related quality of life, and risk for death. Few studies have investigated the relation of electronic health literacy (e-health literacy) to outcomes or the mechanism by which they may be related. Methods: Secondary data were drawn from participants in a larger study on chronic disease self-management who were age 40 years and older, had at least one chronic health condition and a health literacy score of 8th grade or below on the validated short form of the Rapid Estimate of Adult Literacy in Medicine. Participants completed the e-Health Literacy Scale (eHEALS), the Multidimensional Health Locus of Control scale, a modified version of the Attitudes Toward Health Care Providers Scale (ATHCPS), the Wake Forest Physician Trust Scale (WFPTS), and the Gonzalez-Lu adherence questionnaire. Hypothesized relations were evaluated in a bootstrapped path analytic model using the Mplus statistical software. Key Results: Participants included 334 individuals (mean age: 57.5 years; 173 women and 161 men) with Black, Indigenous, and People of Color accounting for 83.3% of the participants and White individuals making up 16.7% of the participants. Model results showed that after controlling for age, education, gender, and race, the eHEALS score was significantly related to the ATHCPS and WFPTS but not to the Gonzalez-Lu adherence questionnaire (p < .05). The eHEALS score was significantly related to the Multidimensional Health Locus of Control scale. Analysis of indirect effects showed that a portion of the relation between e-health literacy and patient attitude and adherence was mediated by internal locus of control (all p < .05). Conclusions: In this study, e-health literacy was related to important patient attitude and behavior variables via locus of control. This finding has implications for the importance of improving patients' ability to use the internet to access and effectively use health information. [HLRP: Health Literacy Research and Practice. 2023;7(2):e80-e88.]